(untitled) (Research, Society and Development, 2020)
For the propagation of seedlings by cutting it is important to select an appropriate substrate. Additionally, the use of humic substances can stimulate the growth of the plants, as is already known for many species. We aimed to investigate the influence of substrates based on carnauba bagana and carbonized rice husk associated with humic substance - HS in the production of Spondia purpurea L. seedlings by cuttings. We studied three proportions (v:v) of substrates, namely, 100% carbonized rice husk; 50% carnauba bagana + 50% carbonized rice husk; 100% carbonized rice husk and four doses of the humic substance, namely, 0 g L-1; 12.5 g L-1; 25 g L-1; 50 g L-1. The experiment was arranged in a completely randomized design, in a 3x4 factorial with four replicates. There was a significant effect of HS doses and substrate interaction and HS doses on the leaf area and dry mass of the aerial part of seedling seedlings. Root volume was affected in isolation by the factors tested. The interaction responses between the substrate and doses of humic substance infer that they act in different ways on development of seriguela seedlings according to the type of substrate, therefore, it is essential to identify and choose the compiled that favors the best results. There is then a need test other substrates associated with the addition of HS, already known to condition the increase of seriguela seedlings produced by cuttings.